Microsurgery Fellowships—Development of a Clinical Curriculum - Rostom, Mai; Lam, Wee-Leon (Journal of Reconstructive Microsurgery, 2018)
Background Microsurgery fellowships have become an integral part of every plastic surgery training program. While each subspecialty differs in terms of reconstructive requirements, the basic tenets and skill sets remain the same. We explore the possibility of designing a clinical curriculum for microsurgery that can provide residents and fellows with a more foundational and structured approach to microsurgical training.Methods Thirteen core and desired skills to accommodate an “ideal” microsurgery curriculum were listed and categorized according to the level of difficulty. The curriculum was then sent to plastic surgery trainees, fellows, and consultants within Scotland in the form of a survey. They were asked to assign a level of difficulty, basic, intermediate, or advanced, to each of the 13 skill sets.Results A total of 27 surgeons were surveyed; the majority of which were plastic surgery registrars. Overall a broad, generic clinical curriculum was felt to be lacking, but would be beneficial at the start of training. The curriculum should emphasize a step-wise progression, starting from achieving competency in safe, efficient anastomosis at the basic level to eventually mastering the principles of complex reconstruction at a more advanced level.Conclusions A generic clinical curriculum offers a framework for tracking progress, the potential for competency-based assessment, and aid in designing a microsurgery fellowship. The curriculum should reflect the evolving nature of the specialty and provide a foundational platform for future innovations.
Keywords: education; microsurgery; development; training; fellowships; teaching